2016
DOI: 10.1039/c5sc03568f
|View full text |Cite
|
Sign up to set email alerts
|

Bond-bending isomerism of Au2I3: competition between covalent bonding and aurophilicity

Abstract: Two isomers, different only by bond angles, are discovered for Au2I3–, due to competition between aurophilic interactions and covalent bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 76 publications
5
17
0
1
Order By: Relevance
“…[64][65][66][67][68] We have shown that for tetramers or larger cluster anions, we can achieve optimal cooling. For example, we were able to completely eliminate vibrational hot bands in Au 4 and other larger cluster anions, 32,[68][69][70][71] whereas extensive hot bands were observed for Au 2 in our previous high-resolution PE imaging study. 72 The spectrum taken at 2.6810 eV [ Fig.…”
Section: B High-resolution Pe Images Of C 2 P −mentioning
confidence: 68%
“…[64][65][66][67][68] We have shown that for tetramers or larger cluster anions, we can achieve optimal cooling. For example, we were able to completely eliminate vibrational hot bands in Au 4 and other larger cluster anions, 32,[68][69][70][71] whereas extensive hot bands were observed for Au 2 in our previous high-resolution PE imaging study. 72 The spectrum taken at 2.6810 eV [ Fig.…”
Section: B High-resolution Pe Images Of C 2 P −mentioning
confidence: 68%
“…There are two types of isomers of Au 2 I 3 – observed with acute (72.0°) and obtuse (100.7°) Au–I–Au angles. 25 Very interestingly, these isomers are called BBIs, which are quite different from other type of isomers. Inspired by this work, we wonder if the BBIs existed in Au n Cl n +1 – ( n = 2–4) cluster ions.…”
Section: Resultsmentioning
confidence: 99%
“…10 Aurophilic interaction has an energy between those of van der Waals force and covalent bonding and plays an important role in stabilizing Au(I) compounds. 11,12 Pyykkö and co-workers theoretically investigated the aurophilic interactions between closed shell Au(I) cationic centers over the past years. 1316 They suggested that the nature of aurophilic interactions can be understood as a dispersion effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 76 Isomerism is an important concept in small organics, and this concept has been found in Au clusters ( Fig. 7A ), 80 , 81 suggesting that clusters might be as versatile as small organics. Clusters also provided insights into chemical bonds.…”
Section: Other Snmsmentioning
confidence: 85%